2016
DOI: 10.11604/pamj.supp.2016.25.1.6172
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis B virus co-infection among HIV-seropositive persons attending antiretroviral clinics in the Eastern Region of Ghana

Abstract: IntroductionHepatitis B and HIV infections are endemic in sub-Saharan Africa including Ghana. Understanding the extent of the co-infection is critical to the optimal care of persons living with HIV and AIDS (PLHIV). We determined the prevalence and risk factors of HBV co-infection in PLHIV and assessed the knowledge of health care workers (HCW) in Antiretroviral Therapy (ART) clinics regarding the co-infection.MethodsA cross sectional study was conducted in five ART clinics to obtain data from a systematic ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 23 publications
(32 reference statements)
4
13
0
1
Order By: Relevance
“…This can be explained by the fact that most women get screened for HIV during pregnancy as part of their pre-natal examination in order to curb mother to child transmission. As reported by previous studies, gender was not a risk factor for HBV infection ( P = 0.953) [ 3 , 11 13 ]. Conversely, Diwe et al in Nigeria reported that men were at higher risk of HBV infection than women due to sharing of injection equipments amongst drug addicts [ 14 ].…”
Section: Main Textsupporting
confidence: 71%
“…This can be explained by the fact that most women get screened for HIV during pregnancy as part of their pre-natal examination in order to curb mother to child transmission. As reported by previous studies, gender was not a risk factor for HBV infection ( P = 0.953) [ 3 , 11 13 ]. Conversely, Diwe et al in Nigeria reported that men were at higher risk of HBV infection than women due to sharing of injection equipments amongst drug addicts [ 14 ].…”
Section: Main Textsupporting
confidence: 71%
“… Kubio et al [ 28 ] 2012 Report review Northern Blood donors NS 33 30.3 NS Low 6. Kye-Duodu [ 29 ] 2012 Cross-sectional Eastern HIV clinic 40.8 320 8.8 67.9 Medium 7. Sagoe et al [ 30 ] 2012 Cross-sectional Greater Accra HIV clinic ≥18 138 13.0 71 % High 8.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the robustness of the HIV/HBV coinfection prevalence results, we performed a leave-one-out sensitivity analysis by iteratively removing one study at a time while recalculating the coinfection prevalence rate. The weight of the individual summaries on the pooled effect showed that the prevalence estimate was dominated by Walana et al [ 31 ], Archampong et al [ 35 ] and Kye-Duodu [ 29 ] (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Results from earlier studies showed that age proves to be the most vital factor in all epidemiological studies of HIV and HBV [56,60,61]. Age-specific HIV/HBV co-infections revealed a higher prevalence among age groups 41-60 years (9.1%) compared to other age groups.…”
Section: Hiv/hbv Co-infectionmentioning
confidence: 95%